Biological Diversity Act, 2002: India’s Lost Decade - Yeshwanth Shenoy (Journal of Traditional and Folk Practices (JTFP), 2013)
India is a land of rich biodiversity and harbours two of the eighteen biodiversity hot spots viz. the Western Ghats and Eastern Himalayas. After the Convention on Biological Diversity (CBD) conservation, sustainable utilization and benefit sharing of Biodiversity has gained utmost importance. The present communication focuses on the provisions of CBD, the Biological diversity Act 2002, the National Biodiversity Authority and its associated organizations and the role they have to play for the benefit of various stakeholders.